Nilai-Nilai Ekonomi Islam Dalam Religiusitas Masyarakat Melayu - Saiful Bahri (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
This study will describe implemented Islamic economics in Malay life. As such a tradition includes by Islam religion, this community will enough for applying a part or comprehensive obedience such as zakah and so on.